Reverse cardiac remodeling after coronary bypass surgery among coronary heart disease patients with Q-wave myocardial infarction in anamnesis - I. V. Timofeeva; S. G. Sukhanov; A. V. Tuev; I. N. Ryamzina (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To compare reverse remodeling process after coronary bypass surgery (CBS) in coronary heart disease (CHD) patients with and without Q-wave myocardial infarction (Q-IM) in anamnesis. Material and methods. The study included 133 CHD patients after CBS; mean age - 56,03±8,90 years. According to Q-IM presence, all participants were divided into two groups: Group I (n = 71) - patients without MI in anamnesis (61,97%; n = 44) or with non-Q-MI (38,03%; n = 27); Group II (n = 62) - patients with Q-MI in anamnesis. All participants underwent echocardiography for three times: before surgery; in early (4,2±1,3 days later) or longterm post-surgery period (2,53±1,31 years later). Results. Positive dynamics in cardiac structure and function among CHD patients after CBS was registered regardless of MI presence in anamnesis. Nevertheless, dynamics intensity differed in patients with non-Q-MI and Q-MI in anamnesis. Early significant increase in ejection fraction (EF) and decrease in abnormal local contractility index were observed in individuals with large infarction zones, due to multiple zones with restored local contractility. In long-term follow-up, volume parameters returned to baseline, but in patients with Q-MI, significant EF improvement persisted. Conclusion. Positive influence of CBS on myocardial contractility in patients with Q-MI in anamnesis persisted in long-term post-surgery period.